From Anderson to ORDAC: A History of Bibliographic Policy Discussion in Australia. Issue 1 (2nd January 2019) - Hider, Philip
ABSTRACT: This article presents a history of national bibliographic policy discussion in Australia, from the turn of the twentieth century to the present day, assessing the contribution this discussion has made to the development of international bibliographic standards. In earlier times, various factors worked against progress towards standardisation and policy innovation, including the extant Anglo-American codes and inherited bibliographic conventions, the difficulties of establishing a national cataloguing agency, and the tyranny of distance experienced by national cataloguing committees. In the mid-twentieth century, Australian cataloguers became more involved in international bibliographic developments, but it was the advent of Machine Readable Cataloguing (MARC) cataloguing in Australia, in the 1970s and 1980s, that gave them a much stronger voice both within and outside the country, as records became much more sharable. Tensions between institutional and individual cataloguing views were eased through the establishment of the Australian Committee on Cataloguing, which represented both, while a broader level of engagement was successfully fostered by the Cataloguers Sections of the Library Association of Australia. This engagement has weakened in recent times, but this is symptomatic of a more general trend towards the globalisation of cataloguing and metadata, whereby national policy discussions are less relevant than are discussions in particular domains.